Human Abuse of Nature and Ecological Repentance in Two Selected Short Stories in Kompas: An Ecocritical Reading - Caesarine, Regina Dhea; Ericha, Fransiska; Dewi, Novita (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the imagination of environmental crisis which refers to water and land as the givers of life, nature as an object controlled by humans, the imagination of ecological repentance by the characters, and apocalyptic narratives in literary works. The data source for this research is the two short stories "Ia Tahu Cara Memusnahkannyaâ€ by Sandi Firly (2021) and the short story "Simuladistopiakoronakra" by Seno Gumira Ajidarma (2020) with the theme of the environment and epidemics. Using qualitative methods which are commonly applied in the study of literary texts, the research data was collected through library study. An eco-critical perspective is used in dissecting the issues of environmental damage and epidemics that are represented in the two short stories. The results show that nature is imagined as life-giving especially water and land. Next, nature is depicted as an object controlled by humans. Finally, the two short stories represent the imagination of the apocalypse and the charactersâ€™ represent. The results of this research may help readers to reflect on ecological conversion through these two short stories.